Traditional hill paddy cultivation practices among the kenyah ethnic in sarawak - Robin, Tunung; King, Jie Hung; Alan, Ribka; Lepun, Philip; Daud, Adrian; Rosli, Anita; Abang Abai, Dayang Shobihah; Ismail, Zahora; Magiman, Mohamad Maulana (Human Resource Management Academic Research Society, 2023)
The Orang Ulu community in the state of Sarawak, Malaysia has cultivated hill rice as the main source of food for generations. The traditional practice of hill paddy cultivation does not require large amounts of water and periodic fertilization. However, due to the trend of agricultural development that requires quick cash returns to meet current socio-economic needs, the practice of hill paddy cultivation is also affected and faces the threat of change. Therefore, documenting information about the culture and traditional practices is important to ensure that the knowledge related to the unique method of hill paddy cultivation can be preserved for future generations. Thus, this study identifies and documents the culture and practices in the cultivation of hill rice among the Kenyah ethnic group. The sampling approach used face-to-face interviews and observation methods involving three Kenyah villages in Belaga and Tatau districts, Sarawak. Based on the results, the hill paddy cultivation process involved important phases such as area selection, land clearing, drying, burning, clearing debris, planting rice and side crops, weeding, harvesting, post-harvest and storage. In conclusion, this study can be used as a source of reference for the Kenyah ethnic traditional practices in hill paddy cultivation in Sarawak.